Factors associated with drug use among adolescents - Peloso, Mirene; Freitas, Brunnella Alcantara Chagas de; Henriques, Bruno David; Marques, Samuel de Souza Magalhães; Lima, Luciana Moreira (Ciência e Natura, 2022)
The study aimed to identify factors associated to drug use in adolescents. For this purpose, it has been observed 133 adolescents registred in ninth grade in two municipal schools in Viçosa, who answered an individual questionnaire validated by PAHO / WHO, applied by members of the Uncensored Extension Project of the Federal University of Viçosa (UFV). Substance use and family structure were evaluated. Statistical tools were: Epi-Info 7.0 StatCalc, Pearson's chi-square test, Poisson regression and SPSS version 23.0 and Stata 9.0 programs. The sample had an average of 15 years old, that 26.3% reported drug use, thus, 65,4% related family history of drug use and low education. Other aspects of family structure included: good family perception, absence of violence and family mental disorder by 78.2%, 82.7% and 75.9% of adolescents, respectively. Only males persisted as a factor associated with drug use, with 2.4 times higher use (PR 2.39; 95% IC 1.19-4.78; p = 0.014). Therefore, only the male gender showed a higher risk for drug use, and further studies are needed to evaluate factors associated with drug use, aiming to promote public health.